2009
DOI: 10.2174/156800909788486722
|View full text |Cite
|
Sign up to set email alerts
|

Immunology of Gynecologic Neoplasms: Analysis of the Prognostic Significance of the Immune Status

Abstract: Gynecologic Oncology has changed in the last few decades. An increasing proportion of patients is benefiting from long term survival although patients diagnosed with advanced disease suffer from a poor prognosis. Unfortunately, several recent studies are confirming that changing the combinations of "traditional" cytotoxic drugs is unlikely to obtain a real breakthrough in survival rates. Furthermore, there is discouraging data regarding consolidation therapies. It is, therefore, necessary to identify new targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 295 publications
(392 reference statements)
1
10
0
Order By: Relevance
“…The systemic effect of neoadjuvant chemotherapy on the immune system deserves to be accurately investigated. Several researchers have dedicated their attention to cancer immune response in order to identify prognostic factors and immunological targets [29]. In a recent study, Denkert and al reported that it is possible to identify a subgroup of breast carcinomas that is characterized by a lymphocytic infiltrate In the tumor tissue and a particularly strong response to chemotherapy [30,31].…”
Section: Resultsmentioning
confidence: 99%
“…The systemic effect of neoadjuvant chemotherapy on the immune system deserves to be accurately investigated. Several researchers have dedicated their attention to cancer immune response in order to identify prognostic factors and immunological targets [29]. In a recent study, Denkert and al reported that it is possible to identify a subgroup of breast carcinomas that is characterized by a lymphocytic infiltrate In the tumor tissue and a particularly strong response to chemotherapy [30,31].…”
Section: Resultsmentioning
confidence: 99%
“…Although our results suggest that important players in the adaptive immune system do not seem to have an influence on survival, these results need to be confirmed (or rejected) by future research. Attempts have been made to identify tumor associated antigens as possible targets in vulvar carcinoma [38]. Hopefully, this will lead to more research concerning targeted therapy in an approach to improve prognosis of vulvar carcinoma patients.…”
Section: Discussionmentioning
confidence: 99%
“…Many tumor-associated antigens, such as squamous cell carcinoma antigen and cancer antigen 125, have been used not only in the differential diagnosis of gynecologic tumors but also as prognostic tools, to assess therapeutic response and detect recurrence [10]. Immunohistochemistry offers some assistance in differentiating between CL and malignant disease.…”
Section: Discussionmentioning
confidence: 99%